2013
DOI: 10.5194/acp-13-1-2013
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the O + OH reaction in hydroxyl nightglow modeling

Abstract: Abstract. The hydroxyl nightglow has been examined anew using calculated rate constants for the key reactive and inelastic O + OH(v ) quenching processes. These constants have been obtained from quasiclassical trajectories run on the adiabatic ab initio-based double many-body expansion-IV potential energy surface for the ground state of the hydroperoxil radical. Significant differences in the vertical profiles of vibrationally excited hydroxyl radicals are obtained relative to the ones predicted by Adler-Golde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 68 publications
2
22
1
Order By: Relevance
“…(15) is proportional to the vibrationally dependent coefficient of Eq. (16), growing in the direction of the smaller v, as is well known from earlier results of modeling and measurements (e.g., Sivjee and Hamwey, 1987;Lopez-Moreno et al, 1987;McDade, 1991;Adler-Golden, 1997;Xu et al, 2012;Caridade et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…(15) is proportional to the vibrationally dependent coefficient of Eq. (16), growing in the direction of the smaller v, as is well known from earlier results of modeling and measurements (e.g., Sivjee and Hamwey, 1987;Lopez-Moreno et al, 1987;McDade, 1991;Adler-Golden, 1997;Xu et al, 2012;Caridade et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…59,60 Recently, Carty et al 5 reported measurements of the rate constant for the O + OH reaction in the temperature range 39 ≤ T/K ≤ 142 and observed no variation with temperature, which led them to conclude that it would largely remain constant between 39 K and 10 K, temperatures typical of cold interstellar clouds. A review 61 on complex-forming reactions like O + OH and a recent application of rate constants calculated 62 for the latter on DMBE IV to model the OH nightglow in the atmosphere 63 are also available.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for OH(ν < 5) collisions with O( 3 P), which are considered completely inelastic, we used the rate coefficient 5 × 10 −11 cm 3 s −1 from Caridade et al (2013). The rate coefficient for the reaction O( 1 D) + N 2 (0) (Reaction R5 in Table 1) was taken from Sander et al (2011) with accounting for the fact that 33 % of the electronic energy is transferred to N 2 (Slanger and Black, 1974) producing, on average, 2.2 N 2 vibrational quanta.…”
Section: Collisional Rate Coefficientsmentioning
confidence: 99%